SKILLS IN ADOLESCENTS AND ADULTS WITH INTELLECTUAL DISABILITIES: TOWARDS INDEPENDENT LIVING WITHIN THE SOCIETY (Proceedings of International Conference on Special Education, 2015)
After reaching adulthood most of the individuals with intellectual disabilities drop out from school/workshop or if employed from employment. The main aim of this research is to explore the skills needed for the adolescents with intellectual disabilities to function as economically and socially independent individuals in the society. This is a pilot study conducted in Prague, Charles University (Czech Republic). 16 teachers, 16 parents and 2 employers were given questionnaires and interviewed to elicit their views about the skills taught to adolescents with intellectual disabilities in the schools and the relevance of the skills learnt in helping the adults function independently in the society. The findings show that though the adolescents are trained in work behaviour, independence skills, production skills, interaction skills, social skills, self help skills and academic skills actual on the job training is required for the individuals with intellectual disabilities. During the research process it was also found that the employers of the individuals with intellectual challenges appoint them only because there is a government policy in the Czech Republic which insists on it or else the employer has to pay compensation of kc 49,000/- per year.